THE SEMANTIC ORGANIZATION OF TERMS DENOTING CRIMES AGAINST AUTHORITIES - Manzhos, Yaroslava (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
The article gives the seme analysis of English legal terms denoting crimes against states, namely terms, denoting crimes against authorities; shows the structure of an element of the lexico-semantic field CRIME AGAINST STATE – the subfield CRIMES AGAINST AUTHORITIES. The detailed analysis of this subfield and its structural parts has been provided.